Decision Support System for Selection of Suitable Mariculture Site in the Western Part of Java Sea, Indonesia - W. Windupranata; R. Mayerle (Journal of Engineering and Technological Sciences, 2009)
Mariculture (marine aquaculture) has been intensified and has created essential  employment  opportunities  over  the  last  two-decades  in  Indonesia,  as well as many other countries in the world. This development has negative impact to  the  environment.  Considerable  amounts  of  nutrient  waste  in  dissolved  and particulate  form  were  released  by  intensive  fish  farming  into  the  environment through  feed  excess,  soluble  fish  excretion  and  faeces  production.  One  of  the first steps to  avoid the dangerous environmental impacts is careful site selection to  minimize  environmental  impacts  arising  from  the  farming  activities (sustainability) as well as to guarantee adequate conditions from the operational point of view (suitability).The paper focuses on the development of a Decision Support System  (DSS) as a tool for the appropriate selection of mariculture   site location. The DSS is based on  physical,  chemical  and  sediment  criteria  as  well  as  on  data  of  conflicting coastal use. The GIS analysis results in a map indicating the suitable areas for the improved  method  of  offshore  cage  mariculture.  In  this  study,  emphasis  was placed on finfish species; however the methods and results may be employed for other species as well following some modifications.The DSS was applied for the  western part of Java Sea, Indonesia. The data were acquired  from  direct  field  measurement,  numerical  modeling  and  existing information  from  particular  agencies.  Numerical  modeling  was  used  to  obtain spatial  and  temporal  distributions  of  hydrodynamic  parameters  (i.e.  current velocities  and  water  levels).  The  Delft3D  modeling  system  (Delft  Hydraulics, The Netherlands) was employed for this purpose. The DSS was developed under GIS  application  of  ESRI®  ArcGISâ„¢  using  weighted  overlay  method.  The results  showed  the  adequacy  of  the  system  for  supporting  governmental authorities in the implementation, environmental controlling, and estimation  of overall carrying capacity for environmental sustainable marine fish farming.